Digitalisasi Pelayanan Akta Kelahiran Anak di Kabupaten Ogan Komering Ulu Selatan - Rina Zahratunnisa (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Riau, 2022)
Digitizing Child Birth Certificate Services in Ogan Komering Ulu Selatan Regency is a step taken by the Population and Civil Registration Office of Ogan Komering Ulu Selatan Regency to advance services in the field of Population Administration. The purpose of this study was to find out how the digitization of Child Birth Certificate services in Ogan Komering Ulu Selatan Regency went, as well as to find out the inhibiting factors of the implementation of digitization. This study uses the success theory of Service Digitization by Indrajit (2004) which is seen from 3 indicators such as Aspects of Support, Ability, and Value. This study uses a qualitative research type with a descriptive approach. The results of the research from the Digitization of Child Birth Certificate Services have not run optimally.